Different computer-assisted sperm analysis (CASA) systems highly influence sperm motility parameters - Boryshpolets, S; Kowalski, R K; Dietrich, G J; Dzyuba, B; Ciereszko, A (Theriogenology, 2013)
In this study, we examined different computer-assisted sperm analysis (CASA) systems (CRISMAS, Hobson Sperm Tracker, and Image J CASA) on the exact same video recordings to evaluate the differences in sperm motility parameters related to the specific CASA used. To cover a wide range of sperm motility parameters, we chose 12-second video recordings at 25 and 50 Hz frame rates after sperm motility activation using three taxonomically distinct fish species (sterlet: Acipenser ruthenus L.; common carp: Cyprinus carpio L.; and rainbow trout: Oncorhynchus mykiss Walbaum) that are characterized by essential differences in sperm behavior during motility. Systematically higher values of velocity and beat cross frequency (BCF) were observed in video recordings obtained at 50 Hz frame frequency compared with 25 Hz for all three systems. Motility parameters were affected by the CASA and species used for analyses. Image J and CRISMAS calculated higher curvilinear velocity (VCL) values for rainbow trout and common carp at 25 Hz frequency compared with the Hobson Sperm Tracker, whereas at 50 Hz, a significant difference was observed only for rainbow trout sperm recordings. No significant difference was observed between the CASA systems for sterlet sperm motility at 25 and 50 Hz. Additional analysis of 1-second segments taken at three time points (1, 6, and 12 seconds of the recording) revealed a dramatic decrease in common carp and rainbow trout sperm speed. The motility parameters of sterlet spermatozoa did not change significantly during the 12-second motility period and should be considered as a suitable model for longer motility analyses. Our results indicated that the CASA used can affect motility results even when the same motility recordings are used. These results could be critically altered by the recording quality, time of analysis, and frame rate of camera, and could result in erroneous conclusions.
Keywords: ryby; Fishes; Image J; Sperm velocity; Male; počítačové zpracování obrazu; Semen Analysis; Animals; Image Processing, Computer-Assisted; mužské pohlaví; Fish spermatozoa; Sperm Motility; CRISMAS; zvířata; Hobson Sperm Tracker; motilita spermií; analýza spermatu